A social-economic burden of rhinosinusitis with nasal polyps with comorbid asthma and influence of dupilumab - I. S. Krysanov; V. S. Krysanova; V. Yu. Ermakova (Качественная клиническая практика, 2021)
Rhinosinusitis with nasal polyps (RwNP) is a one of most common comorbidities in asthma and contrariwise and can lead to exacerbation of severe asthma (SA). Dupilumab is a perspective medicine for treatment of both, because it decreases exacerbations and prevents of a necessity of surgeon. Economics aspects of dupilumab treatment in RwNP + SA are not examined yet. Thus aim of this study was evaluation of social-economic burden of RwNP + SA in the Russian Federation and dupilumab influence on it. Materials and methods. Direct medical (cost of medicines, treatment in outpatients department and in hospital, including surgery and rate of exacerbations per year) and non-medical (payment for temporary and stable disability) and indirect costs (GDP loses) in RwNP + SA patients have been evaluated. Medical cure of a patient with RwNP + SA was created according to survey of experts from different regions of Russia. Modelling of expenditures was prepared on all calculated cohort of potential patients with RwNP + SA from “State” position and growing approach. Results. Expenditures for cure of one patient with RwNP were as 234 217,71 RUR/year. Weighted average costs for one patient with RwNP + SA were 1 881 883,39 RUR, and mostly were associated with indirect costs. Dupilumab can decrease expenditures for one patient with RwNP + SA till 1 593 162,87 RUR (on 15,3 %) annually. Potential cohort with RwNP + SA has been estimated above 39 thousand patients. Total economic burden of RwNP + SA in Russia were estimated as 1,7 bln RUR. Dupilumab usage in patients with RwNP + SA fixed in Register can help decrease economic burden on 259 mln RUR annually. Hidden economic burden of comorbidity can reach 73,4 bln RUR (for all calculated / modelled cohort of patients with RwNP + SA), dupilumab saves 11,3 bln RUR annually in this scenario. Conclusion. Comorbid pathology — RwNP+SA has a sufficient social-economic burden in Russia, that could be decreased by modern biologic drugs, in particular, with dupilumab.